Pelatihan pembuatan LKPD dengan pendekatan CRT bagi guru SDN 2 Prambanan Kabupaten Klaten - Nela Rofisian; Putri Zudhah Ferryka; Isna Rahmawati; sri suwartini (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2025)
This community service program provided training for elementary school teachers at SDN 2 Prambanan, Klaten, to develop student worksheets (Lembar Kerja Peserta Didik/LKPD) aligned with the Culturally Responsive Teaching (CRT) approach within the Merdeka Curriculum. The training aimed to strengthen teachers’ knowledge and skills in designing CRT-based LKPD. Nineteen teachers participated. The program employed Participatory Action Research (PAR) consisting of three stages: (1) demonstration of CRT-oriented LKPD design, (2) guided practice and mentoring, and (3) discussion and reflection. Teachers produced LKPD drafts in small groups and presented their work for peer and facilitator feedback. Product quality was assessed using an LKPD rubric. The results indicate that teachers were able to apply CRT principles in worksheet development, with an average score of 84.4%, categorized as very good. Participants also reported high engagement and expressed confidence to integrate the CRT approach in classroom learning. Overall, the training strengthened teachers’ competence in designing contextual and culturally responsive learning materials for elementary education.